Pengaruh Kualitas Pelayanan Dan Citra Perusahaan Terhadap Kepuasan Pelanggan Pada KPR BTN Cabang Kupang - Jenifa Carejeira Lopes; Petrus E. De Rozari; Maria Indriyani Hewe Tiwu (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This study aims to find out and explain the quality of service and the company's image towards customer satisfaction in KPR BTN Kupang branch. The type of research used by the researcher is quantitative research using primary data. This research was conducted at PT. Bank Tabungan Negara, Tbkl. Kupang Branch. The sampling technique used in this study is to distribute questionnaires (questionnaires). The data analysis techniques used include validity tests, reliability tests, and regression analysis using SPSS analysis tools. The results of this study show that the results of multiple linear regression tests, service quality variables and the image of the State savings bank (BTN) company have a significant effect on customer satisfaction.